Transcranial Magnetic Stimulation: A Scoping Review - Di Feo, Gian; Adeniran, Fahdlullahi; Gannon-Day, Kobe; Zanetti, Anthony; Emond, Micheal; Ghassemkhani, Kassra (Advances in Social Sciences Research Journal, 2026)
Background: Transcranial magnetic stimulation (TMS) has gained increasing recognition as a non-invasive neuromodulatory technique with potential therapeutic applications in dementia and related neurocognitive disorders. This scoping review examined the literature from 1985 through 2023 to evaluate how TMS has been applied across dementia subtypes, which forms of stimulation and neuroimaging techniques have been most frequently used, and what cognitive outcomes have been observed. Method: A systematic search of PubMed, PsycArticles, and PsycInfo yielded 184 articles, of which a subset met inclusion criteria requiring the application of TMS alongside neuropsychological testing. Results: The results demonstrated a striking predominance of Alzheimer’s disease, which accounted for nearly three-quarters of included studies, while vascular dementia, frontotemporal dementia, and Lewy body dementia were rarely addressed. Neuroimaging integration was limited, with the majority of studies not incorporating it; when applied, EEG, MRI, and fMRI were most frequently paired with TMS. Cognitive outcomes were overwhelmingly positive, with 52.9% of studies reporting strong improvements and 44.1% reporting very strong improvements in standardized neuropsychological measures. Notably, no study reported null or adverse effects. Repetitive TMS emerged as the most widely used modality, followed by high-frequency rTMS, whereas deep TMS, low-frequency rTMS, intermittent theta burst stimulation, and bifocal TMS were applied only sporadically. Chi-square analyses revealed no significant associations between dementia type and TMS form or between dementia type and cognitive outcomes, suggesting that observed benefits may generalize across diagnostic subgroups. Discussion: The findings indicate that TMS may enhance cognitive function in dementia regardless of subtype or stimulation protocol, though methodological inconsistencies and limited neuroimaging integration restrict interpretability. Conclusion: TMS appears to be a robust and reproducible intervention for enhancing cognition in dementia, but standardized protocols and larger.